2015
DOI: 10.5194/angeo-33-1421-2015
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of GPS ionospheric scintillations and ionogram spread F over Sanya

Abstract: Abstract. We analyze the data recorded during December 2011-November 2012 by a digital ionosonde and a GPS (Global Positioning System) scintillation and (total electron content) TEC receiver collocated at Sanya (109.6 • E, 18.3 • N; dip lat. 12.8 • N), a low-latitude station in the Chinese longitude sector, to carry out a comparative study of ionospheric scintillations and spread F. A good consistency between the temporal variations of GPS scintillation (represented by the S4 index) and of ionogram spread F (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…In addition, the spread F occurrence and its global distribution are studied from F3/C satellite data, particularly from the occultation measurements of the GPS signal scintillation. This investigation is similar to a local study of spread F and scintillations over Sanya by Zhang et al (2015), who showed that spread F and large scintillations occur simultaneously. As the second objective, we verify that the new method of spread F velocity measurements based on continuous Doppler sounding gives values consistent with previously published results based on different methods of measurement and that these values properly describe the reported longitudinal differences.…”
Section: Introductionsupporting
confidence: 88%
“…In addition, the spread F occurrence and its global distribution are studied from F3/C satellite data, particularly from the occultation measurements of the GPS signal scintillation. This investigation is similar to a local study of spread F and scintillations over Sanya by Zhang et al (2015), who showed that spread F and large scintillations occur simultaneously. As the second objective, we verify that the new method of spread F velocity measurements based on continuous Doppler sounding gives values consistent with previously published results based on different methods of measurement and that these values properly describe the reported longitudinal differences.…”
Section: Introductionsupporting
confidence: 88%
“…Also, the FSF occurrences observed at different sites exhibited distinct local time distribution patterns. Previous studies have also observed this trend (Zhang et al 2015;de Jesus et al 2010de Jesus et al , 2016 Figure 6 shows variations in the average RSF occurrence rates at the four sites. The RSF occurrence rate was much larger than the FSF occurrence rate at GZ; however, the rates were smaller than the FSF occurrence rates at BJ and CC.…”
Section: Nocturnal Seasonal and Solar Activity Variations On Spreadsupporting
confidence: 72%
“…To display ionograms, both the raw and processed (SAO) data were loaded into the SAO Explorer software. In addition, the spread-F index QF, known as the mean spread of the diffusing F layer trace, was obtained by the ARTIST directly from the ionograms using the SAO explorer (Galkin et al, 2008;Zhang et al, 2015) and this was also used in this study to analyze the spread-F signatures. The mean range spread refers to the averaged spread range of all frequencies that detect a diffuse echo in an ionogram (Zhang et al, 2015).…”
Section: Ground-based Ionospheric Irregularity Identificationmentioning
confidence: 99%
“…In addition, the spread-F index QF, known as the mean spread of the diffusing F layer trace, was obtained by the ARTIST directly from the ionograms using the SAO explorer (Galkin et al, 2008;Zhang et al, 2015) and this was also used in this study to analyze the spread-F signatures. The mean range spread refers to the averaged spread range of all frequencies that detect a diffuse echo in an ionogram (Zhang et al, 2015). The spread range at each frequency is the virtual height difference between the top and bottom of the spread echo at a particular frequency (Abdu et al, 2012;Zhang et al, 2015).…”
Section: Ground-based Ionospheric Irregularity Identificationmentioning
confidence: 99%
See 1 more Smart Citation